ANALISIS PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL PNS DI LEMBAGA PEMERINTAHAN DAERAH - Zainur Ihsan; Wulan Purnama Sari; Yeni Yeni (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine the influence of job satisfaction and motivation on the organizational commitment of civil servants at the Sintang Regency Community Empowerment and Village Government Service. This type of research is associative research with a quantitative descriptive approach. The sample for this research was 35 people consisting of civil servants from the Community Empowerment and Village Government Service of Sintang Regency. In this research there are two independent variables, namely motivation and job satisfaction (X1 and X2) and one dependent variable, namely organizational commitment (Y1). The results of this research show that Job Satisfaction and Motivation simultaneously have a significant effect on Organizational Commitment. Furthermore, from the results of the partial test, job satisfaction has a partial effect on organizational commitment, but motivation has no partial effect on organizational commitment at the Community Empowerment Service and Village Government of Sintang Regency.